Factors affecting on quality of life in patients suffering from spinal cord injuries caused by natural and/or man-made disasters: A qualitative meta-synthesis study - Saeed Nazari; Zahra Farsi; Mansoreh Jafarkhani (فصلنامه ابن سینا)
Background: Spinal cord injury causes many physical, psychological, and social consequences for patients and can affect their quality of life. This study aimed to investigate the factors affecting the quality of life of patients suffering from spinal cord injuries caused by human-made disasters and/or natural disasters. Materials and methods: This meta-synthesis qualitative study was performed in 2019-2020. All studies with qualitative methods that had focused on the quality of life in patients with spinal cord injury were assessed between 1995 and 2018. English and Persian electronic databases including PubMed, Medline, Scopus, CINHAL, Blackwell Science Direct, Mdconsult, Pedro, ProQuest, Cochrane Database of Systematic Reviews, SID, Magiran, Iranmedex, and Google Scholar search engine were used to search "quality of life", "spinal cord injury", "human-made disaster" and/or "natural disaster", “qualitative research”, “qualitative study”, "content analysis", "concept analysis", "thematic analysis", "grounded theory", "phenomenology", "ethnology", "historical research", "mixed-methods", and "meta-synthesis" keywords. All studies analyzed and similar themes and sub-themes were emerged. Results: Totally, 18 articles were extracted; nine articles related to the topic were analyzed. The five main themes mentioned in the studies included autonomy, employment, emotional and psychological status, quality of life, and coping that indicating their importance for patients suffering spinal cord injury. Conclusion: The ability of patients to participate in collaborative work and decision making were reduced during the initial stages of spinal cord injury that is due to physical, psychological, and environmental constraints. Holistic approach and pay attention to all dimensions of patients with spinal cord injuries are recommended.